CHANGES IN SELF‐EFFICACY AND OUTCOME EXPECTANCY AS PREDICTORS OF ANXIETY OUTCOMES FROM THE CALM STUDY. Issue 8 (11th March 2014) - Brown, Lily A.; Wiley, Joshua F.; Wolitzky‐Taylor, Kate; Roy‐Byrne, Peter; Sherbourne, Cathy; Stein, Murray B.; Sullivan, Greer; Rose, Raphael D.; Bystritsky, Alexander; Craske, Michelle G.
<x xml:space="preserve">Abstract</x> Background Although self‐efficacy (SE) and outcome expectancy (OE) have been well researched as predictors of outcome, few studies have investigated changes in these variables across treatments. We evaluated changes in OE and SE throughout treatment as predictors of outcomes in a large sample with panic disorder, generalized anxiety disorder, social anxiety disorder, or posttraumatic stress disorder. We hypothesized that increases in SE and OE would predict reductions in anxiety and depression as well as improvement in functioning. Methods Participants (mean age = 43.3 years, SD = 13.2, 71.1% female, 55.5% white) were recruited from primary care centers throughout the United States and were randomized to receive either Coordinated Anxiety Learning and Management (CALM) treatment – composed of cognitive behavioral therapy, psychotropic medication, or both – or usual care. SE and OE ratings were collected at each session for participants in the CALM treatment (n = 482) and were entered into a structural equation model as predictors of changes in Brief Symptom Inventory, Anxiety Sensitivity Index, Patient Health Questionnaire (PHQ), and Sheehan Disability Scale outcomes at 6, 12, and 18 months after baseline. Results The best‐fitting models predict symptom levels from OE and SE and not vice versa. The slopes and intercept of OE significantly predicted change in each outcome variable except PHQ‐8. The slope and intercept of SE significantly predicted change in each outcome variable. Conclusion Over and above absolute level, increases in SE and OE were significant predictors of decreases in symptoms and increases in functioning. Implications for treatment are discussed, as well as future directions of research.